The Long-Term Effects of Group-Based Psychological Interventions for Children With Tourette Syndrome: A Randomized Controlled Trial. Issue 3 (May 2018) - Dabrowski, Julia; King, John; Edwards, Katie; Yates, Rachel; Heyman, Isobel; Zimmerman-Brenner, Sharon; Murphy, Tara
Abstract: This randomized controlled trial examined the long-term effects of group-based psychological interventions on measures of tic severity, self-reported quality of life (QOL), and school attendance. Children ( n = 28) with Tourette syndrome (TS) were assessed 12 months after completing a course of either group-based Habit Reversal Training (HRT) or Education. Both groups demonstrated long-term improvement in tic severity and QOL, which included significant continued improvement during the follow-up (FU) period. Both groups also showed significant posttreatment improvement in school attendance. Further research is required to explore potential therapeutic mechanisms, independent or mutual, which may underlie long-term symptom improvements. Highlights: Group HRT and group Education showed long-term improvement in tic severity and QOL. Both groups demonstrated significant long-term improvement in school attendance. Group treatment may be considered a reasonable alternative to individual treatment. Education may be a suitable alternative to behavioral treatment.